Runtime Verification Second International Conference, RV 2011, San Francisco, CA, USA, September 27-30, 2011, Revised Selected Papers - Khurshid, Sarfraz; Sen, Koushik; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Conference on Runtime Verification, RV 2011, held in San Francisco, USA, in September 2011. The 24 revised full papers presented together with 3 invited papers, 4 tutorials and 4 tool demonstrations were carefully reviewed and selected from 71 submissions. The papers are organized in topical sections on parallelism and deadlocks, malware detection, temporal constraints and concurrency bugs, sampling and specification conformance, real-time, software and hardware systems, memory transactions, tools; foundational techniques and multi-valued approaches.
Keywords: Computer science; Software engineering; Computer software; Logic design; Computer Science; Software Engineering; Algorithm Analysis and Problem Complexity; Logics and Meanings of Programs; Programming Techniques; Programming Languages, Compilers, Interpreters; Mathematical Logic and Formal Languages